Development and application of a method for ivory dating by analyzing radioisotopes to distinguish legal from illegal ivory. (August 2018) - Schmidberger, Andreas; Durner, Bernhard; Gehrmeyer, David; Schupfner, Robert
Highlights: Age determination of ivory by 14-C analysis provides ambiguous findings. Precise age determination possible with subsequent 90-Sr and 228-Th/232-Th analysis. Fast and cheap 90-Sr extraction from ivory via ion chromatography. Providing a method to distinguish between legal and illegal ivory. Abstract: The age determination of elephant ivory provides necessary and crucial information for all criminal prosecution authorities enforcing the Convention on International Trade in Endangered Species of Wild Fauna and Flora. The knowledge of the age of ivory allows to distinguish between pre-convention, hence legal material and ivory deriving from recent, illegal poaching incidents. The commonly applied method to determine the age of ivory is radiocarbon dating in the form of bomb pulse dating, which however will fade out soon. This work provides an enhancement of the radiocarbon dating method by supplementary determination of the isotope profile of 90-Sr and the two thorium isotopes 228-Th and 232-Th. This combined analysis allows for a precise and unambiguous age determination of ivory. We provided calibration curves for all involved radionuclides by analyzing ivory samples with known age and investigated a new method for the extraction of strontium from ivory.